Brief for the higher education of the negro - Miller, Kelly, 1863-1939 (Salt Lake City, UT : Project Gutenberg, 2021)
"Brief for the Higher Education of the Negro" by Kelly Miller is a scholarly discourse written in the early 20th century, specifically around the early 1900s. This publication outlines the critical need for higher education among African Americans, arguing against the pervasive stereotypes that limit their potential. It serves as a social and educational manifesto, advocating for the uplifting and empowerment of the Negro community through advanced learning and leadership. In this work, Miller addresses the historical context of African Americans as subjugated individuals, often considered incapable of higher intellectual pursuits. He argues that education plays a crucial role not only in individual upliftment but also in the overall progress of the race. Stressing the importance of both higher and industrial education, Miller emphasizes that educated leaders are necessary to guide and educate the masses. He uses examples from institutions like Howard University and figures like Booker T. Washington to illustrate the benefits of higher learning. Overall, Miller's treatise is a powerful call to action for the recognition of the Negro's abilities and the imperative of educational investment to foster self-reliance, moral integrity, and social responsibility. (This is an automatically generated summary.)
Release date is 2021-04-10
Charlene Taylor, Martin Pettit and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: African Americans -- Education